2015
DOI: 10.1038/nn.4085
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of C9orf72 dipeptide repeat toxicity connect nucleocytoplasmic transport defects to FTD/ALS

Abstract: C9orf72 mutations are the most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Dipeptide repeat proteins (DPRs) produced by unconventional translation of the C9orf72 repeat expansions cause neurodegeneration in cell culture and in animal models. We performed two unbiased screens in Saccharomyces cerevisiae and identified potent modifiers of DPR toxicity, uncovering karyopherins and effectors of Ran-mediated nucleocytoplasmic transport, providing insight into potential dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
591
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 562 publications
(614 citation statements)
references
References 27 publications
(30 reference statements)
20
591
2
1
Order By: Relevance
“…Whether these neurons represent an early C9orf72-related pathological transition stage or a consequence of surgery, local tissue hypoxia, or epilepsy remains unclear. If these neurons reflect C9orf72 disease, nuclear TDP-43 depletion could have resulted from diminished TDP-43 expression or restricted access to the nucleus due to nucleocytoplasmic transport impairment (Freibaum et al, 2015;Jovicic et al, 2015;Zhang et al, 2015). Further work is needed to determine whether loss of nuclear TDP-43 in the absence of a TDP-43 inclusion relates to particular C9orf72-specific inclusions, as suggested in a recent study (Cooper-Knock et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Whether these neurons represent an early C9orf72-related pathological transition stage or a consequence of surgery, local tissue hypoxia, or epilepsy remains unclear. If these neurons reflect C9orf72 disease, nuclear TDP-43 depletion could have resulted from diminished TDP-43 expression or restricted access to the nucleus due to nucleocytoplasmic transport impairment (Freibaum et al, 2015;Jovicic et al, 2015;Zhang et al, 2015). Further work is needed to determine whether loss of nuclear TDP-43 in the absence of a TDP-43 inclusion relates to particular C9orf72-specific inclusions, as suggested in a recent study (Cooper-Knock et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Although it remains unclear whether such defects caused by DPRs precede TDP-43 pathology, it has been suggested that DPR accumulation may precede TDP-43 accumulation in some C9-FTD patient brain. 34 Together with the fact that genes in the nucleocytoplasmic transport pathway are genetic modifiers of DPR toxicity in yeast, 17 these findings collectively raise the intriguing possibility that DPRs may disrupt nucleocytoplasmic transport independent of the HRE RNA.…”
Section: Since Only Ran[gdp] Is Imported Into the Nucleus Ifmentioning
confidence: 97%
“…[15][16][17] Cytoplasmic mislocalization and aggregation of nuclear proteins in ALS/FTD Protein aggregation is a pathological hallmark of neurodegenerative diseases including ALS/FTD, Alzheimer's, Parkinson's, and Huntington's diseases. 18 Cytoplasmic mislocalization and aggregation of TDP-43 (TAR DNA-binding protein of 43 k D ) is observed in >95% of ALS cases and »45% of FTD.…”
Section: C9orf72-mediated Als/ftdmentioning
confidence: 99%
See 2 more Smart Citations